Individual Differences in Personality Moderate the Effects of Perceived Group Deprivation on Violent Extremism: Evidence From a United Kingdom Nationally Representative Survey - Rottweiler, Bettina; Gill, Paul (Frontiers in Psychology, 2022)
Numerous studies argue that relative group deprivation is a risk factor for radicalisation and violent extremism. Yet, the vast majority of individuals, who experience such circumstances do not become radicalised. By utilising models with several interacting risk and protective factors, the present analysis specifies this relationship more concretely. In a large UK nationally representative survey (n = 1500), we examine the effects of perceived group-based deprivation on violent extremist attitudes and violent extremist intentions, and we test whether this relationship is contingent upon several individual differences in personality. The results show that stronger group-based injustices lead to increased support for and intentions to engage in violent extremism. However, some of the effects are much stronger for individuals who exhibit a stronger need for uniqueness and for status and who demonstrate higher levels of trait entitlement. Conversely, several effects are lessened for those individuals high in trait forgiveness, demonstrating a strong capacity for self-control and for those who are exerting critical as well as open-minded thinking styles, thus constituting buffering protective factors, which dampen the adverse effects of perceived group injustice on violent extremism. The results highlight the importance of considering (a) the interaction between individual dispositions and perceptions of contextual factors (b) the conditional and cumulative effects of various risk and protective factors and (c) the functional role of protective factors when risk factors are present. Collectively, the results bring us one step closer to understand who might be more vulnerable to violent extremism as well as how. Overall, the study suggests that preventing and countering violent extremism (P/CVE) programs must take account of the constellation of multiple factors that interact with (and sometimes enable or disable) one another and which can be targeted in preventions strategies.